2004
DOI: 10.1080/02571862.2004.10635069
|View full text |Cite
|
Sign up to set email alerts
|

Advances in soil erosion, soil conservation, land suitability evaluation and land use planning research in South Africa, 1978–2003

Abstract: Progress in regard to soil erosion, soil conservation, land suitability evaluation and land use planning in South Africa during the 25 year period 1978-2003 is reviewed, with special emphasis on the role of soil scientists. An attempt has been made not only to give a list of the work done, but to present an interpretive review that could hopefully serve as a reference source for future soil scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 20 publications
1
93
0
Order By: Relevance
“…Our data show that increases in rainfall erosivity have significantly enhanced the amount of soil lost within the TRHR (R = 0.854, p < 0.01), an outcome with clear conservation implications. It is clear that vegetation coverage is a key factor in soil conservation [57,58]; our results show that increases in vegetation cover (measured by NPP) are positively correlated with controlling soil erosion (R = 0.217, p < 0.01). Similarly, the amount of exported P is a function of precipitation and hydrological conditions and is also positively correlated with rainfall erosivity (R = 0.161, p < 0.01); at the same time, the amount of exported P is rarely correlated with precipitation.…”
Section: Climate Changementioning
confidence: 66%
“…Our data show that increases in rainfall erosivity have significantly enhanced the amount of soil lost within the TRHR (R = 0.854, p < 0.01), an outcome with clear conservation implications. It is clear that vegetation coverage is a key factor in soil conservation [57,58]; our results show that increases in vegetation cover (measured by NPP) are positively correlated with controlling soil erosion (R = 0.217, p < 0.01). Similarly, the amount of exported P is a function of precipitation and hydrological conditions and is also positively correlated with rainfall erosivity (R = 0.161, p < 0.01); at the same time, the amount of exported P is rarely correlated with precipitation.…”
Section: Climate Changementioning
confidence: 66%
“…This combination of kaolinite and smectite makes these soils highly prone to disaggregation and compaction (Stern, 1990) (Table 4). The soils at Sites 1 and 2 also have significant quantities of quartz in their clay fractions, which make them extremely prone to diaggregation and subsoil compaction (Laker, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…On this evidence, the Oakleaf soils of Sites 1 and 3 should be highly prone to disaggregation and compaction (Table 3). It has been found that soils with high quartz contents in their clay fractions are found widespread in South Africa (Laker, 2004). In addition, soils with high quartz contents in their clay fractions are extremely prone to disaggregation, crusting and erosion (Bühmann et al, 1996) and also to sub-surface compaction (Moolman & Weber, 1978).…”
Section: Compactibility Of the Soilsmentioning
confidence: 99%
“…Dardis et al (1988) provide a review of soil erosion forms in southern Africa, with a strong focus on gully erosion. More recently Laker (2004) has reviewed soil erosion research since the late 1970s. The national picture is reviewed in Boardman et al (2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%